(untitled) (Hoboken, N.J., 2008)
Growing evidence supports the role of dietary antioxidants in the prevention of many chronic diseases such as cancer and cardiovascular disease. Wheat, the second most important cereal crop in the world, is rich in dietary antioxidants. This book provides the most recent findings to date on wheat antioxidants, their properties, methods for activity estimation, and bioactivity.
Keywords: Antioxidants,Wheat,Chất chống oxi hoá,Lúa mì